The Effect of Lead Chloride on Liver Enzyme Levels in Blood Serum of Japanese Quail Coturnix Coturnix Japonica - Mohammed, Maha I.; Taha, Ameer M. (American Journal of Biology and Natural Sciences, 2025)
The purpose of the current study was to examine the physiological effects of lead chloride (PbCl2) on the Japanese quail's (Coturnix coturnix japonica) liver enzyme levels. Thirty quails of both sexes participated in the study; they were split into three groups of ten birds each at random. For 60 days, distilled water was given to the first group, which acted as the negative control. The second group, which was the initial experimental group, received PbCl2 for 30 days at a dose of 25 mg/kg. The third group, which was the second experimental group, received PbCl2 every day for 30 days at a dose of 50 mg/kg. After 0, 15, 30, and 60 days from the beginning of the experiment, blood samples were collected and the birds were dissected. The birds' serum was tested for the liver enzymes ALT (alanine aminotransferase), AST (aspartate aminotransferase), and ALP (alkaline phosphatase).The experiment's physiological findings showed that, throughout the course of the three periods, the experimental groups' serum levels of the enzymes ALT, AST, and ALP significantly increased in comparison to the negative control groups. The highest significant increase was found in the second experimental group for all parameters.